Impact of preanalytical factors on blood CHI3L1 levels - Comabella, Manuel; Gutierrez, Lucía; Castillo, Mireia; Villar, Luisa M.; Eixarch, Herena; La Puma, Delon; Aroca, Montserrat; Vilaseca, Andreu; Montalban, Xavier; Fissolo, Nicolás (Frontiers in Immunology, 2026)
BackgroundChitinase 3-like 1 (CHI3L1) is a prognostic biomarker in multiple sclerosis (MS). However, its clinical application is limited by a lack of standardized detection methods and concerns about preanalytical variability.ObjectivesThis study aims to evaluate the impact of preanalytical factors (delayed processing of blood and repeated thawing/freezing) on serum CHI3L1 levels. Additionally, we sought to correlate CHI3L1 blood and cerebrospinal fluid (CSF) levels and identified its cellular source in peripheral blood mononuclear cells (PBMCs) from MS patients.MethodsWe used an in-house Single Molecule Array (Simoa) assay to measure CHI3L1 levels in serum, plasma, and CSF from MS patients and controls. The source of CHI3L1 production in PBMCs was determined by flow cytometry.ResultsA strong correlation was found between serum, plasma, and CSF CHI3L1 levels. Serum CHI3L1 levels remained stable with delayed processing up to 6 hours and for up to three freeze-thaw cycles. Monocytes, particularly classical monocytes (CD14++CD16- cells), were identified as the main producers of CHI3L1 in PBMCs.ConclusionsThe study establishes preanalytical guidelines for sCHI3L1 assessment and confirms that blood levels can be as informative as CSF levels. This provides groundwork for the standardized use of CHI3L1 as a biomarker in managing MS patients.